Material Removal Mechanism and Evolution of Subsurface Defects during Nanocutting of Monocrystalline Cu - Bing Liu; Yurong Wang; Haijie Yang (Nanomaterials and Nanotechnology)
Multigroup large-scalenanocutting models of monocrystalline Cu were established by molecular dynamics simulations to investigate the influence of cutting parameters on the material removal mechanism. The formation and distribution of subsurface defect structures were revealed, and the evolution behavior of the complete prismatic dislocation loop was analyzed in depth. It was demonstrated that the chips and machined surface of monocrystalline Cu were mainly formed under the coupling effect of shearing and extrusion forces. A diamond tool with a larger edge radius or a negative rake angle could produce a noticeable suppression on the chip formation. The corresponding relationship between the location of defect atoms and the distribution of von Mises stress was studied, which indicated that the shear stress would become larger at the subgrain boundaries, dislocation lines, and the amorphous atoms than that in their nearby regions. The complete prismatic dislocation loop was formed by cross-slip between two sets of stacking faults; meanwhile, the generated multiple Lomer–Cottrell locks hindered its movement and promoted the work-hardening phenomenon. These research results are of great theoretical value to enrich the nanocutting mechanism and technology of plastic materials.